A new species of Circinaria (Pertusariales, Megasporaceae) from Pakistan - Muhammad Shahid Iqbal; Iram Fayyaz; Najam-ul-Sehar Afshan; Fatima Iftikhar; Abdul Nasir Khalid (Botanica Serbica, 2023)
Circinaria pakistanica sp. nov. is described from the Himalayan moist temperate forests in Pakistan. The morphology, chemistry and ITS sequence support its distinction from other species of this genus. The taxon is characterised by a whitish to blackish grey thallus, greyish white epruinose apothecia, flat to slightly concave areoles, a hymenium 110–200 μm high, large ascospores (22–38 × 18–32 μm) and the absence of pycnidia; it also differs from related species in the ITS region.